MEMAHAMI CINTA DARI NARASI KHALIL GIBRAN, “MARIA MAGDALENA: SAAT PERTAMA BERJUMPA DENGAN YESUS” - Leidi Asterina Lontaan; Glory Virginia Sampel (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2021)
“Mary Magdalen: On Meeting Jesus for the First Time” is one of KhalilGibran's wonderful narratives inspired directly by the stories of Jesus’ life.Gibran's keen imagination allows him to enter the worldview of charactersnarrated by the Gospels, from the new perspective that is rarely imagined.This imagination plays an important role in the way Gibran expresses hisunique ideas about life, both through poetry and narrative. Therefore, thisarticle aims to analyze from the art, spirituality, and theologicalperspectives, the way Gibran 'brings to life' Mary Magdalene’s characterwho 'tells' the story of her encounter with Jesus. Through this narrative,Gibran communicates one important theme of the Gospel, that is love, fromthe point of view of a woman who has met Jesus.